2018
DOI: 10.1124/jpet.118.251645
|View full text |Cite
|
Sign up to set email alerts
|

Safinamide Modulates Striatal Glutamatergic Signaling in a Rat Model of Levodopa-Induced Dyskinesia

Abstract: Safinamide (Xadago) is a novel dual-mechanism drug that has been approved in the European Union and United States as add-on treatment to levodopa in Parkinson's disease therapy. In addition to its selective and reversible monoamine oxidase B inhibition, safinamide through use-dependent sodium channel blockade reduces overactive glutamatergic transmission in basal ganglia, which is believed to contribute to motor symptoms and complications including levodopa-induced dyskinesia (LID). The present study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…[67][68][69] Finally, a recent study in patients with PD demonstrated that a specific neurophysiological measure reflecting non-NMDA glutamatergic activity in the primary motor cortex is abnormally enhanced in dyskinetic patients, but can be normalized by using safinamide, a drug that inhibits glutamate release by blocking voltage-gated sodium channels. 52,70 Figure 1 shows the main alterations in dopaminergic and glutamatergic synapses in the striatum.…”
Section: Glutamatergic Mechanismsmentioning
confidence: 99%
“…[67][68][69] Finally, a recent study in patients with PD demonstrated that a specific neurophysiological measure reflecting non-NMDA glutamatergic activity in the primary motor cortex is abnormally enhanced in dyskinetic patients, but can be normalized by using safinamide, a drug that inhibits glutamate release by blocking voltage-gated sodium channels. 52,70 Figure 1 shows the main alterations in dopaminergic and glutamatergic synapses in the striatum.…”
Section: Glutamatergic Mechanismsmentioning
confidence: 99%
“…A key driver of this overactivity is represented by a dysregulated neurotransmission mediated by glutamate which is released from cortical and thalamic terminals in the striatum and evokes excitatory synaptic events in SPNs. 49 , 50 Safinamide through use-dependent sodium channel blockade reduces overactive glutamatergic transmission in basal ganglia, which play an important role in the development of dyskinesia. Sciaccaluga et al demonstrated that in experimental animals, safinamide was able to delay the onset of dyskinesia but not their severity once induced.…”
Section: Conclusion and Clinical Use Suggestionsmentioning
confidence: 99%
“… 49 Gardoni et al reached a similar conclusion. 50 They investigated the effects of safinamide on the development of dyskinesia in 6-hydroxydopamine (6-OHDA)-lesioned rats and they found that the drug did not halt or delay the priming to levodopa, which underlies the development of dyskinesia, in the rat. However, safinamide did not worsen dyskinesia severity.…”
Section: Conclusion and Clinical Use Suggestionsmentioning
confidence: 99%
“…This might explain why striatal Glu release can sometimes dissociate from AIMs appearance. In fact, in dyskinetic rats chronically treated with the MAO-B and Na V channel inhibitor, safinamide (Gardoni et al , 2018), or intrastriatally perfused with AFDX-116 and PD-102807 (present study) striatal Glu did not rise along with AIMs.…”
Section: Telenzepine In Striatummentioning
confidence: 38%
“…Our study would point to an inhibitory action of telenzepine at M1 receptors on striato-nigral MSNs. To possibly confirm this view, telenzepine also reduced the LID-associated elevation of striatal Glu release (Brugnoli et al , 2016;Gardoni et al , 2018;Ostock et al , 2011;Paolone et al , 2015). In fact, elevation of striatal Glu release might result from striato-nigral MSNs stimulation leading to activation of cortico-basal ganglia-thalamo-cortical loop (Market al , 2004;Marti et al , 2005) and cortico-striatal terminals (Ostock et al , 2011;Paolone et al , 2015).…”
Section: Telenzepine In Striatummentioning
confidence: 94%